Βιβλιοθήκη Δημοσθένους Θωμά Κεραμιντζή εκ Κορυτσάς - Καρακίτσιος, Π. Ελευθέριος; Κεραμιντζής, Νικόλαος Βασιλάκη (Μακεδονικά, 2011)
Fifteen years in eastern North Epirus until today are enough to thrill youabout how the Greeks survived by an organized albanization of Albanianstate. The Greeks of North Epirus giving their and their families’ lives andcausing to their relatives exile, prison or lost of their fortunes, show strongwilling to keep their hellenic identity and their love for their country.One of them named Demosthenes Thomas, who was forced to change hissurname to Keramintzis (by his job), was keeping secretly into his house awhole library full with ethnicistic, historical, theological and scientificalbooks, magazines and newspapers. His son, Vasilakis Keramintzis, kept thissecret too, with his son, Nikolaos, and preserved this library until today, whenwe publicize them.Nikolaos is teacher to Albanian school and has also been teaching the hellenic language for five years to Hellenic Frondistiria, which are beingmaintained by our association «Civilization’s friends» in Thessaloniki, incooperation to Hellenic Consulate in Korytsa.